A comparison of Reduced Beam Section moment connection and Kaiser Bolted Bracket® moment connections in steel Special Moment Frames - Johnson, Curtis Mathias (Kansas State University, 2017)
Of seismic steel lateral force resisting systems in practice today, the Moment Frame has most diverse connection types. Special Moment frames resist lateral loads through energy dissipation of the inelastic deformation of the beam members. The 1994 Northridge earthquake proved that the standard for welded beam-column connections were not sufficient to prevent damage to the connection or failure of the connection. Through numerous studies, new methods and standards for Special Moment Frame connections are presented in the Seismic Design Manual 2nd Edition to promote energy dissipation away from the beam-column connection. A common type of SMF is the Reduce Beams Section (RBS). To encourage inelastic deformation away from the beam-column connection, the beam flange’s dimensions are reduced a distance away from the beam-column connection; making the member “weaker” at that specific location dictating where the plastic hinging will occur during a seismic event. The reduction is usually taken in a semi-circular pattern. Another type of SMF connection is the Kaiser Bolted Bracket® (KBB) which consists of brackets that stiffen the beam-column connection. KBB connections are similar to RBS connections as the stiffness is higher near the connection and lower away from the connection. Instead of reducing the beam’s sectional properties, KBB uses a bracket to stiffen the connection. The building used in this parametric study is a 4-story office building. This thesis reports the results of the parametric study by comparing two SMF connections: Reduced Beam Section and Kaiser Bolted Brackets. This parametric study includes results from three Seismic Design Categories; B, C, and D, and the use of two different foundation connections; fixed and pinned. The purpose of this parametric study is to compare member sizes, member forces, and story drift. The results of Seismic Design Category D are discussed in depth in this thesis, while the results of Seismic Design Category B and C are provided in the Appendices.
Keywords: Reduced Beam Section; Kaiser Bolted Bracket; Special Moment Frames; Lateral Force Resisting System; Beam-column connections; Seismic design